2022
DOI: 10.1111/ene.15551
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of epileptic seizures in multiple sclerosis varies according to time of occurrence and etiology

Abstract: Background and purpose Epileptic seizures occur more often in patients with multiple sclerosis (MS) than in the general population. Their association with the prognosis of MS remains unclear. This study was undertaken to evaluate whether epileptic seizures may be a prognostic marker of MS disability, according to when the seizure occurs and its cause. Methods Data were extracted from a population‐based registry of MS in Lorraine, France. Kaplan–Meier curves and log‐rank tests were used to compare the probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…These results are somewhat different compared to very recent data showing no different disease progression in MS patients with an initial epileptic seizure compared to controls. 11 Unlike to our cohort, the cohort investigated by Selton et al only included patients with preexisting (although very moderate) disability with an EDSS of 1. We here demonstrated that patients with an abnormal neurological status as measured by the EDSS, compared to patients without any deficit, that is, monosymptomatic, has an influence on the long-term prognosis, which might at least in part explain the different results.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…These results are somewhat different compared to very recent data showing no different disease progression in MS patients with an initial epileptic seizure compared to controls. 11 Unlike to our cohort, the cohort investigated by Selton et al only included patients with preexisting (although very moderate) disability with an EDSS of 1. We here demonstrated that patients with an abnormal neurological status as measured by the EDSS, compared to patients without any deficit, that is, monosymptomatic, has an influence on the long-term prognosis, which might at least in part explain the different results.…”
Section: Discussionmentioning
confidence: 95%
“…3 The effect of epileptic seizures at the onset of MS on disease progression has rarely been investigated so far. In a very recent study by Selton et al, 11 MS patients with epileptic seizures at the onset of MS did not have a different disease progression compared to the MS control group.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations